Analysis on characteristics of shooting competition in 2020 Tokyo Olympics and successful experience of Chinese team - Ma, J. (Journal of Sociology and Ethnology, 2023)
Abstract: Analyzing characteristics of the 2020 Tokyo Olympic shooting competition, summarizing successful experience of Chinese team, can provide references for training. This research analyzes the distribution of medals, the age structure of participating athletes, the performance of the Chinese team in the Tokyo Olympic Games and summarizes the successful experience of the Chinese team in preparing for the Olympics by methods of literature, mathematical statistics, and logical analysis. The results show that the current international shooting competition is very fierce. In recent years, no country has been able to take the first place continuously. In this Olympic Games, European countries are still the international shooting power. Russia and the United States have made rapid progress, while China has shown the most outstanding performance. India, as an emerging force in recent years, has performed abnormally. In terms of age structure, compared with trap and skeet, rifle and pistol athletes are younger and have less training years, as well as the average age of gold medalists among medal winners is younger, especially the Chinese team. Comparing with the previous year, Chinese team has younger participants and better results in the competition. The successful experience of the Chinese team in Tokyo Olympics mainly includes the following aspects. The top-level management system supporting the development of shooting sports through national efforts is the fundamental guarantee for successful participation in competitions. The training concept of the Chinese team is gradually systematized, which is the ideological foundation of scientific training. The Chinese team has developed new methods for athlete selection for this Olympic Games, which is the key to achieving breakthroughs in this competition.